FFECTS OF SONGS AND RHYMES USED TO ENHANCE ENGLISH VOCABULAR FOR 3RD GRADE STUDENTS IN SMALL SCHOOLS: A CASE STUDY OF SAKLONG SCHOOL IN LOMSAK DISTRICT OF PHETCHABUN PROVINCE - Anghirun, Hathaichanok; Humna, Natchaya; Sriraungrith, Anchana (Journal of MCU Phetchaburi Review, 2023)
The objectives of this research were 1) to examine the effectiveness of a training package consisting of songs and rhymes in enhancing English vocabulary for 3rd-grade students in small schools, 2) to assess the learning achievement outcomes in terms of English vocabulary for 3rd-grade students, 3) to compare the learning achievement outcomes of 3rd-grade students' English vocabulary between a pretest and a posttest, and 4) to evaluate the level of satisfaction among 3rd-grade students regarding the training package of songs and rhymes used to develop English vocabulary. The study population consisted of 3rd-grade students at Salong School during the first term of the academic year 2022. A purposive sampling technique was employed to select a sample of 20 students from Grade 3 for the study. The data collection instruments included English songs and rhymes with accompanying exercises, a pretest, a posttest, and a satisfaction questionnaire. The collected data were analyzed using E1/E2, frequency, percentage, mean and standard deviation, and t-test. The findings of the study revealed that 1) the utilization of English songs and rhymed words demonstrated an effectiveness rating of 77.83/76.00; 2) the learning achievement outcomes in terms of English vocabulary for 3rd-grade students had an overall score of 75.67 percent, 3) there was a statistically significant difference (p >.01) in the learning achievement of the students; and 4) the students exhibited a high level of satisfaction ( =4.91, S.D. = .19). This research provided valuable data on the use of songs and rhymes to develop English vocabulary and its impact on student satisfaction, and also supported the development of cost-effective and beneficial teaching approaches for schools with limited resources.